Immunometabolism and male reproductive function: linking inflammation, oxidative stress, and declining fertility - Zhou, Jiedong; Hu, Shian; Ouyang, Yong; Kong, Yucheng; Liu, Min (Frontiers in Immunology, 2025)
BackgroundMale infertility accounts for approximately 50% of all infertility cases, and its pathogenesis is highly complex. Beyond traditional factors such as genetics, endocrine disorders, and infections, growing evidence indicates that dysregulation of immunometabolism plays a pivotal role in the onset and progression of male reproductive dysfunction.ObjectiveThis review aims to systematically elucidate the role of immunometabolism in male reproductive health, focusing on the complex interplay among inflammation, oxidative stress, and metabolic imbalance. Additionally, it seeks to summarize potential therapeutic targets and outline future research directions.MethodsA narrative review was conducted in accordance with the SANRA (Scale for the Assessment of Narrative Review Articles) guidelines. Relevant studies published between January 2010 to March 2025 were retrieved from PubMed, Embase, and Web of Science using keywords such as “immunometabolism,” “testis,” “male infertility,” and “oxidative stress.”ResultsTesticular immune homeostasis depends on the metabolic coordination among Sertoli cells, Leydig cells, and local immune cells. Aberrant immunometabolism disrupts the blood–testis barrier and endocrine balance by enhancing glycolysis, suppressing oxidative phosphorylation, and promoting the accumulation of reactive oxygen species (ROS), thereby impairing spermatogenesis and testosterone synthesis. Systemic metabolic inflammation induced by obesity, diabetes, and gut microbiota dysbiosis further exacerbates testicular dysfunction through the mTOR/HIF-1α signaling axis and the “gut–immune–gonadal axis.” Pharmacological modulation of key immunometabolic regulators, including AMPK, SIRT1, and PPARγ, has been shown to improve sperm quality and hormone levels in experimental models.ConclusionImmunometabolism serves as a crucial mechanistic bridge linking inflammation, oxidative stress, and the decline of male fertility. Future studies integrating multi-omics and spatial analysis technologies are expected to delineate immunometabolic phenotypes associated with male infertility, paving the way for precision diagnosis and personalized therapeutic interventions.